Pembakuan Kosakata Serapan Bahasa Arab dan Keberterimaannya pada Ranah Keagamaan Islam di Media Daring - Umi Kulsum; Azhari Dasman Darnis; Adang Asdari (Institut Agama Islam Negeri Metro, 2026)
This study aims to explain the pattern of standardization of Indonesian vocabulary derived from Arabic, especially those used in the domain of Islamic religion, and its acceptability in online media. This research uses a qualitative-descriptive approach with data in the form of vocabulary used in the domain of Islam in Indonesian taken from religious articles on Islamic websites and corpus linguistics, such as Google Trends and Sketch Engine. Data collection techniques were conducted by means of document review and observation. The results show that the standardization of Indonesian vocabulary derived from Arabic used in the domain of Islamic religion has a low level of acceptability. The low level of acceptance is due to the fact that Islamic religious vocabulary carries ideological nuances, making its standardization considered more appropriate if it follows the form of the source language.